Simulation study on the influence of particle properties on radial and axial segregation in a Freeman rheometer. (16th January 2023) - Shekhar, Shishir; Pereira, G.G.; Hapgood, K.P.; Morton, D.A.V.; Cleary, P.W.
Graphical abstract: Particle distributions at the end of simulation for mixtures of different shapes (spheres – dark blue and cubes - red) which predominantly exhibit, axial (left) and radial segregation (right). Highlights: DEM modeling of segregation of granular mixtures in the FT4 rheometer. Mixtures of cubical particles with differing sizes segregate faster than spherical particles. Binary mixtures with particles of different shapes segregate radially. Mixtures differing in their frictional properties show limited segregation. Flow energy results do not show any significant correlation to segregation. Abstract: Segregation of granular mixtures in the Freeman FT4 rheometer, a specific example of the more general process of segregation induced via a rapidly rotating object, is studied. The granular mixture comprises two sets of particles that can differ in intrinsic (particle-scale) properties, such as their size, shape, density, or friction. The Discrete Element Method (DEM) was implemented to understand how macroscopic segregation evolves, and the focus was on how the aforementioned particle properties influence segregation. While a difference in particle size is the strongest influence on segregation and produces axial segregation, cubical particles can induce significant radial segregation of the bed. Furthermore, it was found that mixtures of only cubical particles (of different sizes) tend to segregate significantly faster, and the particle bed consolidates to a greater extent than for mixtures of spheres (of different sizes). Mixtures of cubes (of the same size and density) with different frictional properties show moderate segregation (with lower friction particles moving to the bottom), while similar mixtures of spheres show no segregation indicating that friction and shape are linked in their influence on segregation. Finally, no direct correlation was found between the flow energy in the FT4 rheometer and segregation.